Ideał barda w twórczości pieśniarskiej Bułata Okudżawy i Jacka Kleyffa - Lewandowska, Olga (Przegląd Rusycystyczny, 2017)
The article is devoted to the analysis of songs of Bulat Okudzhava and Jacek Kleyff. The subject of interests is the question of artistic creation, the role of the artist in society, his relationship to the world and the cosmos. The article describes a series of images, metaphors that reflect the concept of creator, bard — close to people, bringing hope, yet at the same time a lone sage. Extension and deepening of the concepts expressed by bards is examined on the basis of chosen philosophical works of Nicholas Berdyaev and Gabriel Marcel.